Penjadwalan Kemiringan Panel Surya Menggunakan Smart Relay (PLC) Zelio Untuk Mendapatkan Tegangan Optimal - Rochayatun, Tri, Umar, S.T., M.T, Dedi Ari Prasetya,ST (2015)
Indonesia is a tropical country that is crossed by the equator which has a high solar intensity annually. With this potential need for alternative energy development. The solar panel is one of the tools used to produce alternative energy that comes from the sun. The solar panels installed on the house, generally does not change the position. The way to change the position of the solar panel one using penjadwlan tilt the solar panel located on Zelio PLC. This scheduling function that moves the solar panels to follow the sun shifts in accordance with the schedule that has been made. The method used in this research is to utilize the scheduling system contained in Zelio PLC to make solar panels to change position in accordance with a specific time. Is used as an analog potentiometer input to adjust the angle of the solar panel position. So that the solar panels are able to move use DC motor as solar panels. The results showed that the average - average power generated by the solar panels increased by ± 17:41% when compared to the average - average power generated by the solar panels without getting scheduling slope.